Pulse plating of manganese oxide nanoparticles on aligned MWCNT. (March 2015) - Schneider, M.; Weiser, M.; Schrötke, C.; Meißner, F.; Endler, I.; Michaelis, A.
Abstract : In the present study, aligned multiwalled carbon nanotube (MWCNT) arrays were electrodeposited with manganese oxide as electrode material for capacitor application. The electrode material was prepared in a double-stage process. The first stage, the preparation of the MWCNT array on thin nickel foils by chemical vapour deposition is well known and has already been published. This study has its focus on the second step, the electrodeposition of manganese oxide on MWCNT. Electrodeposition was performed by pulse plating of manganese oxide from a manganese acetate electrolyte. The mechanism and kinetics of this deposition process were electrochemically characterised. Additionally, the manganese oxide modified MWCNT arrays were investigated by scanning electron microscopy and Raman spectroscopy. Furthermore, the capacitor performance and the increase in the capacitance of the modified MWCNT arrays were investigated by cyclic voltammetry in a sodium sulphate electrolyte.